Hybrid Communication in the Halal Lifestyle Economy: The Impact of Generative AI on Communicative Practices Among Digital Entrepreneurs - Eko Boediman (ASIAN PUBLISHER, 2026)
The rapid development of generative artificial intelligence (generative AI) has reshaped the landscape of digital entrepreneurship, particularly in value and ethics-based markets such as the halal lifestyle economy. This study examines how generative AI influences the communication practices of digital entrepreneurs operating in halal sectors including fashion, culinary businesses, health, and finance. Using a qualitative case-study approach and thematic content analysis, the research identifies three major shifts. First, the emergence of hybrid communication models that combine human creativity with AI-generated content. Second, changes in the frequency, style, and tone of brand messages tailored to value-driven Muslim audiences. Third, new dynamics in audience interaction, trust-building, and the management of authenticity within AI-assisted communication environments. The theoretical contribution of this study is the introduction of the “faith-aligned automation” model, which illustrates how AI technologies can be utilized without compromising religious and cultural values. The practical implications are directed at content strategists, platform developers, and halal business practitioners seeking to maintain ethical integrity while adopting automation. This study also outlines its limitations and proposes future research directions, particularly concerning AI governance in digital economies that are sensitive to identity.